Research Article Vocational Students’ Perceptions of Using QR Code Flashcards to Enhance Pronunciation in Report Text Based Learning: A Qualitative Study in Vocational EFL Classrooms - Putri Novita Khoirun Nisa (Retain: Journal of Research in English Language Teaching, 2025)
This study explores vocational students’ perceptions of the benefits and challenges of using QR Code flashcards for pronunciation learning through report texts. Pronunciation is an important component of English communication, especially for vocational students who frequently encounter technical vocabulary related to their field of study. However, pronunciation practice often receives limited attention in classroom activities. This study employed a descriptive qualitative design involving fifteen tenth-grade students from a Petroleum Engineering program at a vocational high school in Indonesia. The participants were selected using purposive sampling. Data were collected through classroom observations and semi-structured interviews and analyzed using thematic analysis. The findings reveal that QR Code flashcards were generally perceived as beneficial in supporting pronunciation learning. Students reported that the media provided easy access to pronunciation audio, supported independent practice, increased confidence in pronouncing unfamiliar vocabulary, and helped them read report texts more fluently. The availability of audio models also enabled students to recognize word stress and pronunciation patterns more accurately. Despite these benefits, several challenges were identified. Students experienced technical issues such as unstable internet connections and slow device performance. Linguistic difficulties with technical vocabulary, affective barriers such as shyness and fear of making mistakes, dependence on teacher guidance, and decreased motivation after repeated use were also reported. Overall, the findings suggest that QR Code flashcards can serve as an effective supplementary medium for pronunciation learning in vocational EFL classrooms when supported by appropriate instructional strategies and classroom management.